2019
DOI: 10.3390/ijerph16203788
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Temporal Prediction for the Monitoring-Blind Area of Industrial Atmosphere Based on the Fusion Network

Abstract: The monitoring-blind area exists in the industrial park because of private interest and limited administrative power. As the atmospheric quality in the blind area impacts the environment management seriously, the prediction and inference of the blind area is explored in this paper. Firstly, the fusion network framework was designed for the solution of “Circumjacent Monitoring-Blind Area Inference”. In the fusion network, the nonlinear autoregressive network was set up for the time series prediction of circumja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…In general, the proposed method is essential for the correlation between variables, which is not limited by the examples in the experiment. In fact, the method has been encapsulated as a program in the information management system of an industrial park in Hebei Province [36]. In the information system, multiple variables can be analyzed following the proposed method, from the view of pollutants and positions.…”
Section: Discussionmentioning
confidence: 99%
“…In general, the proposed method is essential for the correlation between variables, which is not limited by the examples in the experiment. In fact, the method has been encapsulated as a program in the information management system of an industrial park in Hebei Province [36]. In the information system, multiple variables can be analyzed following the proposed method, from the view of pollutants and positions.…”
Section: Discussionmentioning
confidence: 99%
“…The study showed that the prediction performance of the proposed model based on the PSO algorithm was better than that of a traditional BP neural network. Bai et al studied the combined prediction method of a shallow nonlinear autoregressive network (NAR) on the basis of BP [45] and proposed the prediction method from time and space dimensions by using shallow networks [46].…”
Section: Single Methodsmentioning
confidence: 99%
“…NARX derives from the time series autoregressive analysis, and it is effective in the reconstitution of the nonlinear systems. The availability of NARX has been proved by various applications [58][59][60].…”
Section: Neuro Units Based On Nonlinear Autoregressive Modelmentioning
confidence: 99%